Tire Shrinker to Dragster - Hudson, Wilson M.; Project Muse. (Texas A & M University Press [distributor], 1968)
Annotation The title of this collection denotes a span from the horse-drawn vehicles with steel tires that had to be shrunk down occasionally, to the cars that accelerate to unbelievable speeds on a drag strip. Society members like to look back at old customs and beliefs but they are quite willing to take into account that urbanization and engineering do not destroy folklife but rather bring about new formations. From tire shrinkers to the folksay of the drag strip; from silver ingots in East Texas to early Irish storytelling; from folklore and the Finnish sauna to mock bidding in Jamaica; from folkways and mores on the University of Texas campus in the 1930s to Dobie as teacher, this miscellany brings together a wealth of Texas folklore.
Description based on print version record.
Keywords: Texas -- Social Life and Customs; Electronic book; Electronic books